Accumulation and distribution of Zn and Mn in soybean seeds after nutrient seed priming and its contribution to plant growth under Zn- and Mn-deficient conditions. (16th March 2017) - Muhammad, Imran; Volker, Römheld; Günter, Neumann
ABSTRACT: Nutrient seed priming is a strategy to increase the seed reserves of mineral nutrients as primary source for mineral nutrition during seedling development and early growth. The present study investigates the effects of zinc (Zn) and manganese (Mn) seed priming on growth and nutritional status of soybean under conditions of Zn and Mn limitation. Nutrient seed priming increased the natural seed reserves for Zn by, approximately, sixfold and by fivefold for Mn; however, 40–60% of the primed nutrients were adsorbed to the seed coat. Zinc seed priming was able to maintain plant growth for 5 weeks in the same way as Zn supply via the nutrient solution. It is concluded that nutrient seed priming offers perspectives to improve seed quality of soybean for early seedling development under limited nutrient supply or availability and needs further investigation on performance under various stress conditions.